A comparative study of combined small-incision cataract surgery with sutureless trabeculectomy versus trabeculectomy using W-shaped incision - Khurana, AK; Chawla, U; Passi, N; Jyoti, A; Archana, A; Yogesh, A (Nepalese Journal of Ophthalmology, 2011)
Introduction: Manual small-incision cataract surgery with trabeculectomy is now an acceptable option in the surgical management of combined cataract and glaucoma uncontrolled with maximum tolerated medical therapy. Objective: To compare the results and complications of combined manual small-incision cataract surgery (SICS) and posterior chamber intraocular lens (PCIOL) implantation with trabeculectomy by sutureless versus W-shaped incision technique. Materials and methods: The study included 30 eyes of 28 patients with senile cataract and primary open-angle glaucoma (POAG) who were randomly divided into two groups. The patients in Group A (n = 15) underwent SICS with sutureless trabeculectomy and those in Group B (n =15) underwent SICS with trabeculectomy using W-shaped incision with one suture. Post-operative evaluation was done at the first post-operative day and thereafter on follow-ups at 1 week, 2 weeks, 4 weeks and 8 weeks. Results: The mean preoperative and postoperative intraocular pressure (IOP) in Group A was 27.33 ± 3.35 mmHg and 16.13 ± 4.30 mmHg respectively and in Group B it was 29.46 ± 6.06 mmHg and 14.66 ± 2.69 mmHg respectively. The mean reduction in IOP after 8 weeks of follow-up in Group A was 12.52 ± 3.59 mmHg and that in Group B was 16.47 ± 3.79 mmHg (p <0.001). Besides this, the uncorrected visual acuity (UCVA) was better in Group B postoperatively with less surgically-induced against-the-rule (ATR) astigmatism. Conclusion: Combined SICS with trabeculectomy using W-shaped incision offers better prospective in terms of glaucoma control and visual performance than sutureless combined surgery. Key words: sutureless trabeculectomy; combined surgery; W-shaped trabeculectomy DOI: 10.3126/nepjoph.v3i1.4272 Nepal J Ophthalmol 2011;3(5):13-18